2013
DOI: 10.1111/tan.12068
|View full text |Cite
|
Sign up to set email alerts
|

Association of KIR genes and HLA‐C alleles with HPV‐related uterine cervical disease in Korean women

Abstract: This study investigated whether killer-cell immunoglobulin-like receptor (KIR) genes and human leukocyte antigen (HLA)-C alleles, receptors and ligands of natural killer cells are associated with the development of human papillomavirus (HPV)-related cervical disease in Korean women. Blood samples from 132 women with HPV-related cervical disease and 159 women without HPV infection were collected for genotyping of KIR genes and HLA-C alleles. Although no relationship was found between KIR genes and HPV-related c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Four casecontrol studies have previously examined the effects of variation at the HLA and KIR locus in women with CIN (2,5,6,10,11). In particular, Wang et al (11) and Martin et al (6) found that specific HLA ligands for inhibitory KIR were associated with modified risk of developing cervical neoplasia.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Four casecontrol studies have previously examined the effects of variation at the HLA and KIR locus in women with CIN (2,5,6,10,11). In particular, Wang et al (11) and Martin et al (6) found that specific HLA ligands for inhibitory KIR were associated with modified risk of developing cervical neoplasia.…”
mentioning
confidence: 97%
“…In particular, Wang et al (11) and Martin et al (6) found that specific HLA ligands for inhibitory KIR were associated with modified risk of developing cervical neoplasia. Song et al (10) found HLA-C*0303 to confer susceptibility to HPV-related cervical disease, whereas HLA-C*01 was protective against HPV-related cervical disease. Our data are in agreement with the previous results on HLA-C group 1 allele involvement in HPV-associated lesion development (6), and are unique in that they were from an Italian population.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Other class I alleles that have shown to decrease HPV-associated cervical disease are: HLA-B*14 [39], B*2705 [43], HLA-B*3503, B*40, B*4006, B*52 [41], HLA-Cw*0202 and HLA-Cw*0401 [43], HLA-C*03 [40], HLA-G*0103 [47], HLA-C*01 [45], and HLA-C*08 [39] (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…3). The alleles HLA-B*3503 and HLA-C*0303 have shown contradictory results, and more information is needed to characterize the true role of these alleles in the outcome of HPV infections [40, 41, 43, 45]. …”
Section: Discussionmentioning
confidence: 99%